EXPERIENCE OF BILATERAL SYNCHRONOUS PERCUTANEOUS NEPHROLITHOLAPAXY (PCNL) (Indonesian Urological Association, 2023)
Objective: This case report will present bilateral synchronous percutaneous nephrolitholapaxy (PCNL) that was performed in Saiful Anwar General Hospital Malang for the first time. Case(s) Presentation: 49 years old male with flank pain on both sides continuously. Non contrast abdominal Computed Tomography (CT) scan showed bilateral pyelum stone and bilateral hydronephrosis. From blood analysis, the creatinine serum was 1.5 mg/dL and ureum serum was level 69.8 mg/dL. Discussion: Bilateral synchronous PCNL was performed in prone position, and stone fragmentation was done with pneumatic lithotripter, the operation last for about 2 hours with minimal amount of bleeding. After 3 months of follow-up, urology ultrasound and abdominal X-ray shows no residual stone, and normal ureum-creatinine level (0.77mg/dL; 43.7mg/dL). Conclusion: Bilateral synchronous PCNL is a safe choice to be done in order to treat bilateral pyelum stone, it can decrease length of stay , total cost therapy, and morbidity of the patient.